Slow Control System for PandaX-III experiment. (10th May 2021) - Yan, X.; Chen, X.; Chen, Y.; Dai, B.; Lin, H.; Li, T.; Han, K.; Ni, K.; Wang, F.; Wang, S.; Zheng, Q.; Zeng, X.
Abstract: The PandaX-III experiment uses high pressure gaseous time projection chamber to search for the neutrinoless double beta decay of 136 Xe. A modular slow control system (SCS) has been designed to monitor all the critical parameters of the experiment. It ensures the proper operation of the experiment and provides necessary information for data corrections. The main subsystems of the experiment will be constantly monitored by the data collection module of the SCS, which collects data from sensors and sends them to the centralized database. When an alarm message is generated by the anomaly detection module, it will be sent to an alert website and related on-call experts immediately. A demonstrator of the SCS has been built for the PandaX-III prototype detector. The long-term test of it provided valuable experience for the final design of the SCS for PandaX-III.